Einige neue Monomere und Polymere - Rolf C. Schulz (CHIMIA)
As an introduction the different chemical methods for obtaining new polymers are reviewed. The ring-opening polymerization of some cyclic acetals can produce well-defined copolymers with regular sequences. By incorporation of C–C double-bonds into the main chain of polyetheracetals chemical modifications and cross-linking of the polymers are possible. Recently, 2-isopropenylnaphthalene became available in technical scale; this new monomer forms homopolymers and blockcopolymers with interesting properties (for instance thermoplastic elastomers). By N-chlorination and N-trifluoroacetylation of polyamides polymeric reagents are obtained which are useful for the oxidation or trifluoroacetylation of low molecular compounds. Because of the good solubility of the N-trifluoroacetyl polyamides they can also be used for the determination of molecular-weights by GPC, light scattering or osmotic pressure as well as for NMR spectroscopy. The N-alkylation of polyamides or polyethyleneimines is a new way for the preparation of branched polymers.